Cardiovascular Outcomes and the Use of Oral Antidiabetic Drugs: A Review of Current Evidence from Observational Studies - Elnaem , M.H.; Mohd Azam, F; Akkawi, ME (IIUM Medical Journal Malaysia, 2020)
Type 2 diabetes mellitus (T2DM) is a major global disease burden that affects millions of people worldwide. The disease is well known to predispose patients to a wide range of macro- and microvascular complications. Cardiovascular complications are common macrovascular consequences among patients with T2DM. The primary goal of T2DM management is to achieve proper glycaemic control that helps to avoid or delay the incidence of disease complications. T2DM management involves the utilisation of oral antidiabetic medications and injectables, including insulin. Hence, we conducted this work to discuss and summarise the cardiovascular outcomes associated with the oral antidiabetic pharmacotherapy prescribed for patients with T2DM. The agents involved were metformin, sulfonylurea, dipeptidyl peptidase-4 inhibitors, thiazolidinediones, alpha-glucosidase inhibitors, and sodium-glucose cotransporter-2 inhibitors. We decided to focus on the findings reported from observational studies published between 2009 to 2019 to provide an updated and more realistic insight on these cardiovascular outcomes associated with the oral antidiabetic drugs in the usual clinical practice.